Eco-Aesthetics and Sustainable Urban Spaces: The Role of Public Art in Enhancing Environmental Consciousness in Nigerian Cities - Idisi, Benjamin Evi; Eleh, Anthony; Oghenejabor, Obaro Dominic (Journal of Science Research and Reviews, 2025)
This study examines the role of eco-aesthetics in promoting sustainable urban spaces through the integration of public art within Nigerian cities. Drawing on a mixed-methods approach, data were collected from a quantitative survey (N = 200) and qualitative interviews (n = 30) to investigate how eco-art influences environmental awareness, social engagement, and aesthetic appreciation. Quantitative findings revealed strong positive perceptions of eco-art in enhancing public consciousness about environmental issues, fostering community participation, and reinforcing cultural identity within urban settings. Complementary qualitative insights highlighted that public artworks served as visual reminders of ecological responsibility, platforms for collective dialogue, and catalysts for local pride. Participants emphasized the ability of eco-art installations to merge functionality with creativity, thereby contributing to the beautification of urban spaces while encouraging pro-environmental attitudes. City-level analyses underscored how variations in socio-economic conditions and urban planning policies shaped the perceived impact of eco-art. The study concludes that eco-aesthetic practices hold significant potential for advancing sustainable urban development in Nigeria, provided they are strategically integrated into planning frameworks. These findings contribute to growing discourse on art, sustainability, and urban transformation, offering both theoretical and practical implications for policymakers, urban planners, and artists